Mercury detection using bamboo sawdust derived flourescent carbon nanoparticles. - Belasa, Denmark O.
Mercury, a notorious heavy metal known for its extreme toxicity and bioaccumulative properties, poses significant threats to human health even at low concentrations. Addressing this critical issue, researchers have been actively pursuing the development of rapid, cost-effective, and sensitive detection techniques. This study focuses on meeting this imperative need by employing bamboo sawdust as a carbon source, combined with urea and water using a hydrothermal method, to synthesize fluorescent carbon nanoparticles (FCNs) under varying reaction temperatures and times. Optimizing the synthesis conditions, the study identified that a reaction temperature or 120 degrees Celsius and a reaction time of 6 hours synthesized the solutions with the highest fluorescence intensity. Characterization of the synthesized solution through SEM-EDS revealed agglomeration, resulting in a particle size distribution of 57 nm to 126 nm, larger than the typical carbon dots size. However, elemental analysis confirmed the presence of Carbon, Oxygen, and Nitrogen, aligning with the expected composition of carbon dots. Further characterization via UV-VIS spectrophotometer and FT-IR analysis exhibited absorbance peaks attributed to molecular transitions and absorption bands peaks related to different functional groups commonly found in carbon dots. Despite the synthesized solution demonstrating fluorescence upon exposure to UV excitation and exhibiting functional groups consistent with those of carbon dots, its limitation in terms of large particle size led to the conclusion that the synthesized solution can be categorized as FCNs. Application of the synthesized to detect Hg2+ in water, excluding other metal ions, demonstrated successful fluorescence quenching by mercury ions. The relationship between Hg2+ concentration and fluorescence quenching followed a linear equation, with a calculated detection limit of 38.50 nM, indicating sensitivity. However, this sensitivity falls short of the maximum allowable mercury concentration in water (10 nM). The study recommends further refinement and optimization of the bamboo sawdust-derived FCNs (B-FCNs) method for enhanced mercury detection applications.